2016
DOI: 10.1016/j.erap.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of international mobility on the attitudes of researchers

Abstract: Academic mobility is usually perceived and discussed as a positive phenomenon-as a prerequisite for building a competitive and successful economy and quality science. Academic mobility has now become essential to building a successful academic career in many research domains. On the policy level the negative impact of academic mobility on researchers' lives and especially women's is usually overlooked and marginalized. In my paper I focus on academic mobility in the context of academics' relationships and fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Answering the second question, researchers found that prior experience of international mobility (e.g., during student years) makes academics more likely to move (Børing et al, 2015;Equeter & Hellemans, 2016) as a result of both reduced uncertainty about what it might entail and a better understanding of the potential benefits. Highly productive academics are more likely to move (Azoulay et al, 2017); the volume of recently published research, rather than its impact, seems to enable mobility (Allison & Long, 1987;Edler, Fier, & Grimpe, 2011).…”
Section: Mobility and Early-career Capital Of Academicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Answering the second question, researchers found that prior experience of international mobility (e.g., during student years) makes academics more likely to move (Børing et al, 2015;Equeter & Hellemans, 2016) as a result of both reduced uncertainty about what it might entail and a better understanding of the potential benefits. Highly productive academics are more likely to move (Azoulay et al, 2017); the volume of recently published research, rather than its impact, seems to enable mobility (Allison & Long, 1987;Edler, Fier, & Grimpe, 2011).…”
Section: Mobility and Early-career Capital Of Academicsmentioning
confidence: 99%
“…In answering the question about the consequences of international mobility, Equeter and Hellemans (2016) found that it leads to higher work engagement and employee well-being. Numerous studies of academic productivity also found that, although international mobility brings a decrease in performance in the short term (Bäker, 2015;Fernández-Zubieta et al, 2015), it is positively related to research productivity in the long term (Veugelers & Van Bouwel, 2015;Zubieta, 2009).…”
Section: International Mobility and Research-career Capitalmentioning
confidence: 99%
See 1 more Smart Citation
“…Work engagement has rarely been studied in the context of job change. Some research has shown low work engagement as an antecedent to voluntary external job change (e.g., de Lange, De Witte, & Notelaers, 2008; Schaufeli & Bakker, 2004), but only de Lange, De Witte, and Notelaers (2008) and Equeter and Hellemans (2016) have investigated the impact of mobility on work engagement. The longitudinal study of de Lange et al (2008) provided evidence that this work-related state of mind improves after an external mobility.…”
Section: Impacts Of Job Mobilitymentioning
confidence: 99%
“…The longitudinal study of de Lange et al (2008) provided evidence that this work-related state of mind improves after an external mobility. Equeter and Hellemans (2016) focused on a specific mobility: the international mobility of researchers (at least 1 month abroad for strictly professional reasons during the last 3 years, without job change or affiliation change). They found that successful international mobility significantly and positively predicts an increase in researchers’ work engagement.…”
Section: Impacts Of Job Mobilitymentioning
confidence: 99%